2016
DOI: 10.1111/dar.12425
|View full text |Cite
|
Sign up to set email alerts
|

Death from liver disease in a cohort of injecting opioid users in a Swedish city in relation to registration for opioid substitution therapy

Abstract: Liver related mortality among opioid users was significantly elevated in OST recipients, showing the long-term importance of chronic liver disease in this population. [Jerkeman A, Håkansson A, Rylance R, Wagner P, Alanko Blomé M, Björkman P. Death from liver disease in a cohort of injecting opioid users in a Swedish city in relation to registration for opioid substitution therapy. Drug Alcohol Rev 2017;36:424-431].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Pawan et al [26] studied the damaging effects of opium use on the liver and lungs in chronic opium addicts in Rajasthan, India, and indicated that longterm and chronic opium use raised the risk of liver and lung damage. Elsewhere, Jerkeman et al [27] carried out a study on death from liver disease in a cohort of injecting opioid users in a Swedish city; they reported that the death rate significantly increased in these people. Thus, seemingly, the inhaled opium brings about inflammatory reactions in the liver more than its oral consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Pawan et al [26] studied the damaging effects of opium use on the liver and lungs in chronic opium addicts in Rajasthan, India, and indicated that longterm and chronic opium use raised the risk of liver and lung damage. Elsewhere, Jerkeman et al [27] carried out a study on death from liver disease in a cohort of injecting opioid users in a Swedish city; they reported that the death rate significantly increased in these people. Thus, seemingly, the inhaled opium brings about inflammatory reactions in the liver more than its oral consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Definitions vary between countries, and each definition has its limitations [ 57 ]. There is a wide range of plausible mechanisms between substance use and death [ 58 , 59 ]. Acute poisoning, chronic organ damage caused by drugs as well as accidents during intoxication may all be considered to be drug-related.…”
Section: Discussionmentioning
confidence: 99%
“…This enables systematic and longitudinal research including NEP patients in the present setting, including follow-up of NEP attendance over time. Several previous research studies from the present setting have originating from the identification of patients attending NEP units in the region [42,[84][85][86].…”
Section: Methodsmentioning
confidence: 99%